Second harmonic ECRH breakdown experiments in the TJ-II stellarator. (30th March 2015) - Cappa, Á.; Ascasíbar, E.; Castejón, F.; Tafalla, D.; Tabarés, F.; Ochando, M.; Romero, J.; de la Cal, E.; Martínez, J.; Nagasaki, K.
Abstract: A summary of the second harmonic ECRH breakdown experiments performed in the TJ-II stellarator is given here. The goal of these experiments is to determine the dependence of second harmonic X-mode plasma breakdown efficiency on several relevant parameters as the EC power, wave polarization, beam injection angle, tokamak-like induced electric field, neutral gas pre-fill pressure and discharge creation time with respect to the ramp-up of the currents in the coils. For each different scenario, the breakdown properties are determined, as well as the initial pressure conditions and the level of initial radiation before the injection of the ECRH power, which plays an essential role in the breakdown process.